Central Pressure Waveform-Derived Indexes Obtained From Carotid and Radial Tonometry and Brachial Oscillometry in Healthy Subjects (2–84 Y): Age-, Height-, and Sex-Related Profiles and Analysis of Indexes Agreement - Zócalo, Yanina; Bia, Daniel (Frontiers in Physiology, 2022)
Aortic blood pressure (aoBP) waveform-derived indexes could provide valuable (prognostic) information over and above cardiovascular risk factors (CRFs). To obtain aoBP waveform-characteristics, several (i) techniques, (ii) recording sites, (iii) pressure-only waveform analysis mathematical approaches [e.g., pulse wave analysis (PWA), wave separation analysis (WSA)], and (iv) indexes [augmentation pressure and index (AP and AIx), forward (Pf) and backward (Pb) components of aoBP, reflection magnitude (RM), and reflection index (Rix)], were proposed. An accurate clinical use of these indexes requires knowing their physiological age-related profiles and the expected values for a specific subject. There are no works that have characterized waveform-derived indexes profiles in large populations considering: (i) as a continuous, data from different age stages (childhood, adolescence, and adulthood), (ii) complementary indexes, (iii) data obtained from different techniques and approaches, and (iv) analyzing potential sex- and body height (BH)-related differences. In addition, (v) there is a lack of normative data (reference intervals, RIs) for waveform-derived indexes. Aims (1) to evaluate the association and agreement between PWA- and/or WSA-derived indexes obtained with different techniques and approaches; (2) to determine the need for sex-, BH-, and/or age-specific RIs; (3) to define RIs for PWA- and WSA-derived indexes in a large cohort of healthy children, adolescents, and adults. Methods 3619 subjects (3–90 y) were included; 1688 healthy (2–84 y). AP, AIx, AIx@75, Pf, Pb, RM, and RIx were obtained (carotid and radial tonometry, brachial oscillometry/plethysmography). The association and agreement between indexes were analyzed (Concordance correlation coefficients, Bland–Altman analysis). Mean and SD equations and sex-specific BH- and age-related profiles were obtained (regression methods; fractional polynomials). Results Waveform-derived indexes were not equivalent; for a specific index, there were systematic and proportional differences associated with the recording site (e.g., carotid vs. radial) and technique (e.g., tonometry vs. oscillometry). The need for sex-, BH-, or age-specific RIs was dependent on the index and/or age considered. RIs were defined for each index considering differences between recording sites and techniques. Equations for waveform-derived indexes age-related profiles were included, enabling to determine for a specific subject, the expected values and potential data deviations.